Geomembrane-Geotextile Interface Friction - Rustam Effendi (Jurnal Teknologi Berkelanjutan, 2012)
In geotechnical constructions incorporating geomembranes and geotextiles, the interfacestrength of the two geosynthetics is of the most concern. Some researchers found considerably low values of the strength from various devices. This research aimed at contributing the interface strength database with a ring shear device for simulating large displacements commonly mobilised in the field when failures occur. The interfacing geomembranes were VLDPE, smooth HDPE, PVC and textured HDPE. Values of residual for the geomembrane-geotextile interfaces were found to be independent of stress level. They vary widely from 6.1 to 33.8 degree, and are controlled mainly by the texture and stiffness of geomembranes, and the types and arrangement of filaments composing the geotextile. The lower value is for a smooth HDPE with a geotextile comprising glossier filaments, while the higher value is mobilised by the textured HDPE against a geotextile with filaments that are best-interwoven. Of all interface combinations, the ring shear tests with a smooth HDPE geomembrane always resulted in lowest residual interface strengths.